Using a participatory curriculum and cascade-training model to empower Ugandan youth to make responsible social, beconomic, sexual and reproductive health decisions (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aims: To demonstrate an integrated, gender-transformative holistic approach to promote youth empowerment and community referral for healthcare in Uganda.Methods: The USAID-funded Fistula Care Plus (FC+) project supported implementation of sexual and reproductive health (SRH) education for in- and out-of-school youth. FC+ used the adapted Aflateen PLUS curriculum, integrating SRH with concepts such as financial and leadership skills and planning for future, FC+ trained and provided continuous supervision support to 19 teachers and 29 peer-educators to facilitate the curriculum to 10 in-school youth clubs and 10 out-of-school youth groups across Jinja and Kamuli Districts.Results: In- and out-of-school youth participating in the Aflateen clubs reached an additional 5,950 community members with SRH and financial savings information and referred 1,364 individuals to health care, including family planning, maternal care, STI testing, and evaluation of fistula symptoms.Conclusion: The Aflateen Plus curriculum’s learner-centered and in-depth engagement approach engages youth to critically think about present and future decisions. The curriculum and club model empowered youth and promoted a culture of information sharing and community referral to reduce vulnerability. Stakeholder engagement (e.g., teachers, peer-educators, local government, and health care sector) increased ownership and sustainability of the intervention.